2010
DOI: 10.1111/j.1600-0714.2009.00814.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of GLUT-1 in the invasion front is associated with depth of oral squamous cell carcinoma and prognosis

Abstract: The present study shows that GLUT-1 served as a marker indicating that tumors with deep invasion tended to result in a worse prognosis in patients due to either lymph node metastasis, a recurrence of the primary lesion or distant metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
63
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 17 publications
6
63
1
1
Order By: Relevance
“…Among the 10 PDSCC cases, only 1 (10%) showed mild staining and 9 (90%) showed intense staining. These findings accord with those of Reisser and Ohba in OSCC (8,13).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Among the 10 PDSCC cases, only 1 (10%) showed mild staining and 9 (90%) showed intense staining. These findings accord with those of Reisser and Ohba in OSCC (8,13).…”
Section: Discussionsupporting
confidence: 82%
“…It has been suggested that altered GLUT-1 expression is the initial change evident in not only OSCC, but also nonsmall cell lung carcinoma and various other carcinomas including those of the esophagus, colon, colorectum, stomach, breast, uterine cervix and pancreas, being positively correlated with aggressive tumor behavior and poor prognosis (8). Furthermore, enhanced GLUT-1 expression has been noted in premalignant lesions (9).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A number of studies have demonstrated a close association between GLUT-1 expression and malignant mesothelium, which is relevant for the clinical behavior of the tumor (14,21,22). The results of the present study indicated that GLUT-1 was overexpressed in pancreatic cancer and was associated with clinicopathological characteristics, including tumor size, clinical stage and lymph node metastasis.…”
Section: Discussionsupporting
confidence: 55%
“…Glucose transporter-1 (GLUT-1) is a member of the GLUT family, which is expressed in erythrocytes, endothelial cells, placenta and blood-tissue barriers, including the blood-brain and blood-nerve barriers (10,11). Recent studies have demonstrated that GLUT-1 is often upregulated in various malignant tumors, including colorectal cancer (12), esophageal cancer (13), oral squamous cell carcinoma (14), renal cell carcinoma (15) breast cancer and lung cancer (16). It is also considered to be the predominantly elevated glucose transporter under ischemic and hypoxic conditions, whereby cells require glycolysis as an energy source.…”
Section: Introductionmentioning
confidence: 99%